Effect of platelet-rich plasma (PRP) on ovarian structures in cyclophosphamide-induced ovarian failure in female rats: a stereological study. (22nd November 2018) - Dehghani, Farzaneh; Aboutalebi, Hamideh; Esmaeilpour, Tahereh; Panjehshahin, Mohammad Reza; Bordbar, Hossein
Abstract: Background: Ovarian failure is diagnosed by ovarian destruction and reducing sex hormonal levels. Platelet-rich plasma (PRP) contains several growth factors that induce tissue repair and may induce folliculogenesis. Objective: This study evaluates the effect of PRP on ovarian structures and function in cyclophosphamide (Cy)-induced ovarian failure in female rats by a stereological method. Methods: Thirty-two adult female rats were divided into four groups (Control, Cy, Cy + PRP, and PRP). Female infertility was induced by Cy (75 mg/kg, single dose, intraperitoneally). Animals were treated by PRP which was obtained from age-matched male rats (200 μL, single dose, intraperitoneally). Blood samples were collected for measurement of hormones. The animals were dissected and the right ovaries were removed, fixed, sectioned, and stained by H&E. Stereological methods were used to estimate cortex and medulla volume, and the number and diameter of follicles, follicular cell, and oocyte using light microscopy. Results: Cyclophosphamide had the maximum effect in decreasing on cortex volume, the pre-antral follicles number, a diameter of follicular cells and oocyte diameter in the antral follicle and the reduction of estradiol and progesterone levels compared with the control group. PRP had a dominant positive effect on the ovarian cortex volume, pre-antral follicles number and antral follicle diameter relative to the control group. PRP also decreased oocyte diameter in pre-antral follicle in infertile animals ( p  < 0.001). Conclusion: It seems that PRP has a protective effect on ovarian failure in the infertile female rat model.